2022
DOI: 10.7759/cureus.23754
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline-Associated Hyperpigmentation: A Case Report and Literature Review

Abstract: Drug-induced hyperpigmentation is an adverse cutaneous effect; it has been associated with several systemic medications. A healthy 40-year-old man developed facial and dorsal hand hyperpigmentation within two weeks of beginning doxycycline monohydrate 100 milligrams twice daily for acne. Skin pigmentation significantly diminished at a follow-up evaluation two months after discontinuing the medication. Doxycycline-associated skin hyperpigmentation, albeit uncommon, has been described in 18 patients in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It is considered harmless but has cosmetic relevance. It typically resolves slowly over time, with drug cessation …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is considered harmless but has cosmetic relevance. It typically resolves slowly over time, with drug cessation …”
Section: Discussionmentioning
confidence: 99%
“…Skin hyperpigmentation/discoloration was a relatively common occurrence, particularly in the later study years. This is a known AE of minocycline . It arises from iron and melanin accumulation extracellularly and within macrophages in the dermis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with facial AV, clinical experience suggests that PIH from truncal AV has a tendency to be more persistent. Furthermore, a recent case report and literature review has reported drug-induced hyperpigmentation associated with doxycycline monohydrate 100 mg twice daily (BID), but it was concluded to be uncommon and, in most cases, resolved after doxycycline was discontinued [ 19 ]. Notably, a review of the published photographs in the aforementioned reference of doxycycline-induced hyperpigmentation showed more diffuse hyperpigmentation that is distinct from the focal follicular/perifollicular PIH that is characteristically associated with AV.…”
Section: Discussionmentioning
confidence: 99%